Analysis of institutional design in supreme audit institutions. Case of Costa Rica - Mora Brenes, Andrea (2014)
This paper aims to understand the progress and setbacks they have experienced the supreme audit institution in Costa Rica in terms of institutional strength / weakness, after the reform in 1994. For this purpose the Organic Law of the Comptroller General of the Republic is analyzed Republic through three dimensions- legal, administrative and functional relationship with the state powers.